miR-484: A Potential Biomarker in Health and Disease - Jia, Yin-zhao; Liu, Jing; Wang, Geng-qiao; Song, Zi-fang (Frontiers in Oncology, 2022)
Disorders of miR-484 expression are observed in cancer, different diseases or pathological states. There is accumulating evidence that miR-484 plays an essential role in the development as well as the regression of different diseases, and miR-484 has been reported as a key regulator of common cancer and non-cancer diseases. The miR-484 targets that have effects on inflammation, apoptosis and mitochondrial function include SMAD7, Fis1, YAP1 and BCL2L13. For cancer, identified targets include VEGFB, VEGFR2, MAP2, MMP14, HNF1A, TUSC5 and KLF12. The effects of miR-484 on these targets have been documented separately. Moreover, miR-484 is typically described as an anti-oncogene, but this claim is simplistic and one-sided. This review will combine relevant basic and clinical studies to find that miR-484 promotes tumorigenesis and metastasis in liver, prostate and lung tissues. It will provide a basis for the possible mechanisms of miR-484 in early tumor diagnosis, prognosis determination, disease assessment, and as a potential therapeutic target for tumors.